Reading Interest and Study Habits as Predictors of Road Pavement Learning Outcomes - Radha Krisnamurti Sigamura; Nanda Prayoga (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2026)
This study examines whether reading interest and study habits predict learning outcomes in the Road Pavement Structure course among sixth-semester Civil Engineering students at Universitas Musi Rawas. The study used a quantitative, non-experimental ex post facto correlational design involving the complete cohort of 32 students in the 2025-2026 academic year. Reading interest was measured using a 29-item Likert questionnaire, study habits using a 23-item Likert questionnaire, and learning outcomes using final-semester examination scores. Descriptive statistics, Pearson correlations, simple regression, and multiple regression were used to analyze the data. The reported results indicate a positive association between reading interest and learning outcomes (r = 0.4388; coefficient of determination = 19.75%) and between study habits and learning outcomes (r = 0.430; coefficient of determination = 18.40%). When entered simultaneously, reading interest and study habits produced a multiple correlation of R = 0.563 and explained 31.554% of the variance in Road Pavement Structure learning outcomes, with F = 9.712 exceeding the reported critical value of 3.33. These findings suggest that academic reading engagement and consistent study routines are relevant non-cognitive contributors to achievement in a technically demanding civil engineering course. The results are interpreted as predictive associations rather than causal effects because the research design was observational. The study supports the integration of structured academic reading, time-management routines, and self-regulated learning practices into engineering instruction.